PERSEPSI PETANI DAN PERAN KELAMBAGAAN PERKUMPULAN PETANI PEMAKAI AIR (P3A) PADA SISTEM IRIGASI USAHATANI PADI SAWAH DI DESA SINDANGKASIH KECAMATAN RANOMEETO BARAT KABUPATEN KONAWE SELATAN - Israwati Israwati; Anas Nikoyan; Putu Arimbawa (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This research is motivated by the observation of a phenomenon occurring in Sindangkasih Village, wherein irrigation systems encounter challenges with water availability during the cultivation of paddy rice plants. The objective of this study is to ascertain the perceptions of farmers with regard to the irrigation system and the role of the Water User Farmers Association (P3A) in the irrigation system. The study population consisted of all P3A members in Sindangkasih Village, numbering 126 individuals. The research sample was determined using the Slovin formula with a degree of error/margin of error of 15%, resulting in a sample size of 33 respondents. The samples were selected through the use of simple random techniques. The data were collected through observation and interviews, with questionnaires used as instruments. The variables under investigation in this study are farmers' perceptions of irrigation systems and the institutional role of the Water User Farmers Association (P3A). This study employed a quantitative methodology. The data were analyzed using descriptive statistics and the class interval formula. The findings indicate that the perception of wet-rice farmers in Sindangkasih Village regarding the irrigation system remains inadequate. Despite the availability of water for the irrigation of rice fields on two occasions per year, damage to one component of the irrigation network will still result in the disruption of the distribution of irrigation water. One consequence of damage to irrigation channels is the uneven distribution of water. The role of the Water User Farmers Association (P3A) has been effectively fulfilled. The role of P3A in Sindangkasih Village is indispensable to members and other farming communities for the management and maintenance of the irrigation system network.